Stress and fracture analysis of short flat bars with projections using boundary element method - Ang, Jarreal Jia Xiang (Nanyang Technological University, 2022)
Mechanical components generally contain geometric discontinuities such as fillet, grooves and sharp edges. These discontinuities are often known as stress raisers since stress concentrates around and caused the local stress to be significantly high. Cracks are likely to initiate and propagate from these high localized stress points. This poses the potential of mechanical components to fail earlier than expected.